The association between pesticide use and cutaneous melanoma: a systematic review and meta‐analysis. (28th October 2019) - Stanganelli, I.; De Felici, M.B.; Mandel, V.D.; Caini, S.; Raimondi, S.; Corso, F.; Bellerba, F.; Quaglino, P.; Sanlorenzo, M.; Ribero, S.; Medri, M.; Farnetani, F.; et al.
Abstract: Background: The incidence of cutaneous melanoma (CM), the deadliest form of skin cancer, has gradually increased in the last decades among populations of European origin. Epidemiological studies suggested that farmers and agricultural workers are at an increased risk of CM because they were exposed to pesticides. However, little is known about the relationship between pesticides and CM. Objectives: To investigate the association between exposure to pesticides and CM by systematically reviewing the literature. Secondary aim was to determine the categories of pesticides mainly involved in CM development. Methods: A systematic review of the literature was performed up to September 2018 using MEDLINE, Embase and Web of Science. Studies assessing CM risk in licensed pesticide applicators were considered. Strict criteria were established to select independent studies and risk estimates; random effect models, taking into account heterogeneity, were applied. A pooled risk estimate for CM was calculated for the use of each type of pesticide and type of exposure. Between‐study and estimate heterogeneity was assessed and publication bias investigated. Results: A total of nine studies (two case–controls and seven cohorts) comprising 184 389 unique subjects were included. The summary relative risks for the categories 'herbicides – ever exposure', 'insecticides – ever exposure', 'any pesticide – ever exposure' and 'any pesticide – high exposure' resulted 1.85 [95% confidence interval (CI): 1.01, 3.36], 1.57 (95% CI: 0.58, 4.25), 1.31 (95% CI: 0.85, 2.04) and 2.17 (95% CI: 0.45, 10.36), respectively. Herbicides and insecticides had no between‐study heterogeneity ( I 2 = 0%), while a significant heterogeneity ( I 2 > 50%) was detected for the high exposure to any pesticide. No indication for publication bias was found. Conclusions: Individuals exposed to herbicides are at an increased risk of CM. Future properly designed observational studies are required to confirm this finding.